SOCIAL SUSTAINABILITY ASSESSMENT OF HOG GROWING BUSINESS AS EXPERIENCED BY HOG GROWERS IN SOUTHWESTERN CEBU PHILIPPINES - Pocong, Felix Q; Bate, Glynne P; Hernandez, Nerissa Mae E; Margallo, Rosalea Fenina A; Comision, Barbara B (Journal of Agriculture and Technology Management, 2023)
This study aimed to investigate the experiences of the smallholder and subsistence hog producers of hog-growing businesses in Southwestern Cebu, Philippines. The population of the study was 16 smallholder hog growers and two subsistence hog producers. Empirical data were collected from the smallholder hog growers. For the purpose of validating the sustainability of the hog-growing business, an interview with the subsistence hog producers was conducted. The findings of the study showed that most of the smallholder pig growers were female and the significant problem in hog growing was waste processing or disposal. The subsistence hog producers had long years of experience; very optimistic about the potential or prospect of hog operation and the social sustainability of the hog growing business. Both smallholder pig producers and subsistence hog producers continue to operate hog production since pork meat demand is high, profitable business help sustain the food supply for the southwestern part of Cebu Island, Philippines, and it is a sustainable industry. The social sustainability indicators considered in this study were job creation, social acceptance, contribution to the local economy, health and safety, and community involvement. Hog growing business contributed to the SDG goals such as no hunger, food security, and decent job; therefore, the hog-growing business is socially sustainable.